Development and validation of a knowledge, attitude, and practice scale for myopia prevention and control among parents of children and adolescents - Ming Cong Cao; Guo Xin Bai; Yu Liu; Xue Wang; Yu He Wang (Frontiers in Public Health, 2026)
Objective To develop a knowledge, attitude, and practice (KAP) scale for myopia prevention and control among parents of children and adolescents, and to test its reliability and validity. Methods Based on the KAP theory, an initial scale was developed through literature review and expert consultations. From March to April 2026, a convenience sample of 500 parents of children and adolescents from kindergartens, primary schools, and secondary schools was surveyed to test the scale’s psychometric properties. The final scale was formed after reliability and validity analyses. Results A total of 477 valid questionnaires were returned. The final scale consists of three dimensions (knowledge, attitude, and practice) with 35 items. The response rates for the two rounds of expert consultation were both 100%, with an authority coefficient of 0.913 and Kendall’s W coefficients of 0.372 and 0.413, respectively. The item-level content validity index (I-CVI) ranged from 0.897 to 0.974, and the scale-level content validity index (S-CVI) was 0.945. Exploratory factor analysis extracted three factors explaining 73.52% of the total variance. Confirmatory factor analysis indicated a good model fit ( χ 2 /d f = 1.836, GFI = 0.908, CFI = 0.936, RMSEA = 0.042). The Cronbach’s α coefficient for the total scale was 0.944, test–retest reliability was 0.918, and split-half reliability was 0.922. Conclusion The developed KAP scale for myopia prevention and control among parents of children and adolescents is well-constructed and exhibits good reliability and validity. It can serve as a valid tool for assessing parents’ KAP levels in this population.